Morphology of the antennal sensilla of two species of Hoplopyga Thomson, 1880 (Coleoptera, Scarabaeidae, Cetoniinae) - Costa,Cleicimar Gomes (2021)
ABSTRACT Antennal sensilla are important functional elements of sensory systems in insects. This study aimed to determine the morphology and structure of the sensilla of two species of the genus Hoplopyga. Adults of Hoplopyga liturata (Olivier, 1789) were collected in traps with sugarcane juice as an attractant. Thereafter, larvae of Hoplopyga albiventris (Gory and Percheron, 1833) were collected in mounds of termites (Cornitermes cumulans (Kollar, 1832) Isoptera). Then, they were reared in the laboratory for adult observations. Antennae of H. liturata and H. albiventris have sensilla chaetica, trichodea, placodea (type I and II), coeloconica (type I and II), and ampullacea (or pore). Females of H. liturata have a total of about 10657 sensilla and males have about 12512, whereas females of H. albiventris have about 16490 sensilla and the males 24565 sensilla. Sensilla placodea are predominant in the antenna of males and females of both species.